Feasibility Analysis of Establishing a Gudeg Jogja Business Using the Net Present Value (NPV) Method in the City of Jakarta - Mutiara Silvia Putri; Fiona Trianandra (Research Collaboration Community (RCC), 2024)
This research aims to analyze the feasibility of establishing a Jogja gudeg business in the city of Jakarta using the Net Present Value (NPV) method. Gudeg, as a typical Yogyakarta culinary specialty, has quite large market potential in Jakarta considering the high public interest in traditional and unique foods. This research will examine various aspects, including technical analysis, financial analysis, and sensitivity analysis. Financial analysis will focus on NPV calculations to measure the added value of investments in the long term. It is hoped that the results of the research will provide a clear picture of the potential success of the Jogja gudeg business in Jakarta and become a reference for prospective entrepreneurs who are interested in the culinary business.